Des pistes de solution pour une meilleure intégration des considérations éthiques en santé publique - Désy, Michel (Can J Public Health, 2014)
Public Health Ethics (PHE) has grown significantly during the past decade. Despite PHE’s relevance, its integration into public health practices, resources, activities and knowledge is lacking. In our view, this lack of integration can be understood as a problem of knowledge transfer (KT). In this article, we briefly describe existing knowledge integration methods and their limitations for PHE. We then explore the KT literature to underline how recent research in this area presents possible solutions to the problem before us. The proposed solutions stress the importance, first, of adapting knowledge and tools to the needs of users and the context of their practice, and, second, of recognizing the personal, continual nature of interactions between actors. We conclude that it would be beneficial to public health organizations to count on the presence and expertise of PHE knowledge brokers in order to build, in partnership with knowledge users, tools that will allow them to achieve PHE integration in public health practices, resources, activities and knowledge.